The Shifting of Language Style of The Main Character in The Wild Robot Film 2024: A Sociolinguistic Approach - Shafira Mutiara Lestari; Tri Arie Bowo; Donal Fernado Lubis (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyze the language style and style-shifting used by the main character, Roz, in the animated film The Wild Robot (2024). This study is conducted through a sociolinguistic approach by using Martin Joos' theory of language style, which includes five categories: Frozen, Formal, Consultative, Casual, and Intimate. In addition, this study also uses Susan Ervin-Tripp's theory of stylistic shift, which includes three main factors: Addressee, Speech Condition, and Rhetorical Shift. The research method used is descriptive qualitative. The data is obtained through the transcription of Roz's dialogue in the film. The results of the 52 data analyzed, with the dominant language style being casual language style as much as 13 data, formal language style as much as 12 data, then consultative language style as much as 11 data, then familiar language style as much as 10, and the last is frozen language style as much as 6 data. shows that Roz experienced a significant development in language style, from a frozen and formal language style to a more relaxed and familiar language style. The analysis also reveals several occurrences of style shifting in the movie. A total of 52 instances of style shifting were identified. Among the influencing factors, speech condition appears most frequently with 47 occurrences, followed by addressee with 32 occurrences, while rhetorical shift appears only once. These shifts mainly occur due to changes in interlocutors and situational contexts, leading Roz to adjust her language style accordingly. This finding proves that language in fictional works such as animated films can reflect complex and representative social dynamics. Thus, this study contributes to expanding the scope of sociolinguistics and confirms that language has an important function in shaping identity and relationships between individuals, even in the context of fictional narratives.